OPPORTUNITIES FOR YOUNG PEOPLE IN UZBEKISTAN - Kayumova Nafisa (Galaxy International Interdisciplinary Research Journal, 2022)
In the Republic of Uzbekistan, people aged 14 to 30 are considered youth. As long as we can inculcate the main factors of increasing the activity of young people in the socio-economic and political-spiritual spheres into the minds of our scientific and creative young intellectuals, we will create the strongest spiritual and educational pillar of the foundation of the Third Renaissance.